2020
DOI: 10.1523/jneurosci.0782-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Olfactory Associative Memory by the Circadian Clock Output Signal Pigment-Dispersing Factor (PDF)

Abstract: Dissociation between the output of the circadian clock and external environmental cues is a major cause of human cognitive dysfunction. While the effects of ablation of the molecular clock on memory have been studied in many systems, little has been done to test the role of specific clock circuit output signals. To address this gap, we examined the effects of mutation of Pigment-dispersing factor (Pdf) and its receptor, Pdfr on associative memory in male and female Drosophila. Loss of PDF signaling significant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 81 publications
(148 reference statements)
1
25
0
Order By: Relevance
“…In Drosophila , synaptic plasticity that regulates sleep was induced by specific sequences of spikes that occur during spontaneous activity in clock neurons ( 12 ). Moreover, based on recent studies, the interaction of light and clock information influences memory learning, possibly mediated by sleep ( 13 , 14 ). These studies made an interesting link between light and clock information in forming neural coding, which is based on “neural activity” of circadian clock networks.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila , synaptic plasticity that regulates sleep was induced by specific sequences of spikes that occur during spontaneous activity in clock neurons ( 12 ). Moreover, based on recent studies, the interaction of light and clock information influences memory learning, possibly mediated by sleep ( 13 , 14 ). These studies made an interesting link between light and clock information in forming neural coding, which is based on “neural activity” of circadian clock networks.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, given that neonicotinoids appear to disrupt circadian rhythmicity, and given that there is circadian regulation of memory formation with time of day influencing performance, neonicotinoid-induced disruption to the clock may contribute to the memory deficits 61 . The time-of-day differences in mushroom body memory are thought to result from day/night differences in PDF and PDFR signalling 30 , therefore the loss sLNv dorsal terminal PDF rhythmic signalling of PDF caused by the neonicotinoids may provide another route to the insecticide induced reductions in memory we report.…”
Section: Discussionmentioning
confidence: 75%
“…Memory formation is also reliant on circadian rhythms 29 , 30 and sleep 31 , 32 . Work in honeybees and bumblebees has shown that neonicotinioids can reduce behavioural rhythmicity and disrupt sleep behaviour in these important pollinators 21 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…This is thought to help them find new foraging patches, as most flowers are nectar-rich in the morning (Bloch et al, 2017). Likewise, Drosophila has been shown to demonstrate time-ofday memories and circadian change in olfaction and olfactory memory (Lyons and Roman, 2009;Chouhan et al, 2015;Flyer-Adams et al, 2020), showing that these behaviors, underlying mechanisms and potential impacts of neonicotinoids can be modeled using this system.…”
Section: Circadian Rhythmsmentioning
confidence: 99%
“…Therefore this study demonstrates that neonicotinoid exposure disrupts the day/night differences in clock neuron synaptic PDF neuropeptide availability and structural plasticity and decreases circadian rhythms. Interestingly, recent work suggests circadian changes in PDF signaling from the sLNv to the mushroom body may mediate time-of-day effects on Drosophila olfactory shock memory (Flyer-Adams et al, 2020). Therefore the disruption of sLNv synaptic PDF neuropeptide levels and structural plasticity may contribute to or be responsible for the deficits in mushroom body mediated olfactory shock memory seen.…”
Section: Circadian Rhythmsmentioning
confidence: 99%